Failing phrenics: an obscure cause of exertional dyspnea: Case report and literature review. Issue 29 (July 2016) - Rafiq, Arsalan; Ijaz, Mohsin; Tariq, Hassan; Vakde, Trupti; Duncalf, Richard
Abstract: Introduction: Idiopathic phrenic nerve palsy is a rare cause of exertional dyspnea. We present a case of a patient presenting with worsening dyspnea of an unknown etiology found to be related to bilateral phrenic nerve palsy. Discussion: Forty-two-year-old man presented to our emergency department with exertional dyspnea, orthopnea, and a left lower lobe consolidation treated initially as bronchitis by his primary physician as an outpatient, then subsequently as pneumonia at another institution, with no improvement in symptomatology. After admission to our hospital, CT chest demonstrated only supradiaphragmatic atelectatic changes. Echocardiography was normal. Bronchoscopy was contemplated however the patient could not lie flat. A fluoroscopic sniff test demonstrated diaphragmatic dysfunction and pulmonary function tests revealed restrictive pulmonary disease with evidence of neuromuscular etiology. Nerve conduction studies confirmed bilateral phrenic neuropathy. He was referred to a specialized neuromuscular disease center where subsequent workup did not demonstrate any specific etiology. A sleep study confirmed sleep disordered breathing suggestive of diaphragmatic paralysis and he was discharged on bi-level positive pressure ventilation. Conclusion: This is a unique case of exertional dyspnea and orthopnea from diaphragmatic paresis caused by bilateral phrenic nerve palsy where the initial workup for pulmonary and cardiovascular etiologies was essentially unremarkable. Shortness of breath and orthopnea caused by phrenic neuropathy is a rare condition, yet has a variety of etiologies. Our case suggests a template to the diagnostic approach, management, and follow up of bilateral phrenic nerve palsy.